1969
DOI: 10.1039/j19690000702
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus–fluorine chemistry. Part XX. Redox disproportionation of difluorophosphines, RPF2, with electronegative substituents R

Abstract: Difluorophosphines, RPF2, containing the electronegative substituents, R = CF, and CsH5, will undergo redox disproportionation with formation of tetrafluorophosphoranes and cyclopolyphosphines, in accord with the overall equation 10 RPF2 --+a-5 RPF4 + (RP),, (n = 4, 5 for R = CF,: n = 5 for R = C6H5). The identity of the products, all previously known, was established by comparison of their physical properties (n.m.r. and mass spectra, i.r. spectra, X-ray powder diagram, etc.) to those of the authentic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…[9] The P III ÀF bond is very strong at 545 kJ mol À1 , [10] and metal complexes have been reported for some R 2 PF ligands. [13] Schmutzler, Riesel, and others [13][14][15][16][17] have thoroughly investigated this disproportionation and found that 1) fluorophosphines such as Ph 2 PF, Me 2 PF, and nBu 2 PF disproportionate readily, [13,14] which essentially precludes their application in catalytic processes that involve ligand dissociation; 2) fluorophosphines with bulky or electron-withdrawing substituents such as (C 6 F 5 ) 2 PF, [15] (CF 3 ) 2 PF, [9,16] and tBu 2 PF [17] are thermally stable. [13] Schmutzler, Riesel, and others [13][14][15][16][17] have thoroughly investigated this disproportionation and found that 1) fluorophosphines such as Ph 2 PF, Me 2 PF, and nBu 2 PF disproportionate readily, [13,14] which essentially precludes their application in catalytic processes that involve ligand dissociation; 2) fluorophosphines with bulky or electron-withdrawing substituents such as (C 6 F 5 ) 2 PF, [15] (CF 3 ) 2 PF, [9,16] and tBu 2 PF [17] are thermally stable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The P III ÀF bond is very strong at 545 kJ mol À1 , [10] and metal complexes have been reported for some R 2 PF ligands. [13] Schmutzler, Riesel, and others [13][14][15][16][17] have thoroughly investigated this disproportionation and found that 1) fluorophosphines such as Ph 2 PF, Me 2 PF, and nBu 2 PF disproportionate readily, [13,14] which essentially precludes their application in catalytic processes that involve ligand dissociation; 2) fluorophosphines with bulky or electron-withdrawing substituents such as (C 6 F 5 ) 2 PF, [15] (CF 3 ) 2 PF, [9,16] and tBu 2 PF [17] are thermally stable. [13] Schmutzler, Riesel, and others [13][14][15][16][17] have thoroughly investigated this disproportionation and found that 1) fluorophosphines such as Ph 2 PF, Me 2 PF, and nBu 2 PF disproportionate readily, [13,14] which essentially precludes their application in catalytic processes that involve ligand dissociation; 2) fluorophosphines with bulky or electron-withdrawing substituents such as (C 6 F 5 ) 2 PF, [15] (CF 3 ) 2 PF, [9,16] and tBu 2 PF [17] are thermally stable.…”
mentioning
confidence: 99%
“…[11] However, no applications of fluorophosphines in catalysis have been described, [12] perhaps because of the instability of R 2 PF with respect to the disproportionation reaction shown in Equation (1). [13] Schmutzler, Riesel, and others [13][14][15][16][17] have thoroughly investigated this disproportionation and found that 1) fluorophosphines such as Ph 2 PF, Me 2 PF, and nBu 2 PF disproportionate readily, [13,14] which essentially precludes their application in catalytic processes that involve ligand dissociation; 2) fluorophosphines with bulky or electron-withdrawing substituents such as (C 6 F 5 ) 2 PF, [15] (CF 3 ) 2 PF, [9,16] and tBu 2 PF [17] are thermally stable. Whether the source of the stability is thermodynamic or kinetic has not been determined (see below).…”
mentioning
confidence: 99%
“…Aryldifluorophosphines are less common compared to aryldichlorophosphines because of their instability towards redistribution to form bisarylfluorophosphines and phosphorus trifluoride, or redox disproportionation to form aryltetrafluorophosphoranes and cyclopolyphosphines [11][12][13][14][15][16][17][18][19][20][21][22][23]. DmpPF 2 (7), however, was isolated as a stable material by a chlorine-fluorine exchange reaction (Eq.…”
Section: Synthesismentioning
confidence: 98%
“…Schmutzler, Riesel, and others13‐17 have thoroughly investigated this disproportionation and found that 1) fluorophosphines such as Ph 2 PF, Me 2 PF, and n Bu 2 PF disproportionate readily,13, 14 which essentially precludes their application in catalytic processes that involve ligand dissociation; 2) fluorophosphines with bulky or electron‐withdrawing substituents such as (C 6 F 5 ) 2 PF,15 (CF 3 ) 2 PF,9, 16 and t Bu 2 PF17 are thermally stable. Whether the source of the stability is thermodynamic or kinetic has not been determined (see below).…”
Section: Dft Calculated Relative Energy Differences (δE) For the Dispmentioning
confidence: 99%